Burnout among pre-medical students in Pakistan - Paracha, Mahrukh Faisal; Sandesh Kumar,; Sachdev, Divesh Sunil (Journal of the Pakistan Medical Association, 2025)
Dear Madam, Burnout is described as a state of mental exhaustion accompanied by fatigue, resulting in poor efficiency, typically occurring when an individual experiences stress over a prolonged period (1). Almost everyone experiences burnout at some point in their lives, but the prevalence is notably higher among high school students (2). Each year, approximately 150,000 Pakistani students sit for the Medical and Dental College Admission Test (MDCAT), with only 10% securing a place in medical school (3). The probability of gaining admission to a public medical college is so low that students often take gap years and reappear for the exam multiple times to secure a seat on merit, as affording medical education at a private college is unfeasible for many due to the exorbitant tuition fees. Students preparing for this highly competitive exam often study for months or years, managing their board exam preparation simultaneously. The fear of not meeting expectations and disappointing others, such as parents, is particularly high during this period. Consequently, it is unsurprising that many students experience burnout. Burnout not only decreases efficiency in daily tasks but also causes emotional turmoil, fatigue, agitation, and low self-esteem. There is a high risk of developing addiction to tobacco and alcohol during this period. Burnout negatively affects memory and thinking skills, interferes with normal sleep patterns, and can lead to insomnia. Decreased performance due to burnout can result in poor scores in critical exams, such as the MDCAT and board examinations, potentially leading to depression (4). A thorough literature search on PubMed and Google Scholar revealed a surprising lack of articles addressing burnout among pre-medical students in Pakistan, particularly given the fact that medicine is a highly revered field in this country. Alarmingly, a significant proportion (75%) of medical students in Pakistan report joining the profession due to external pressures, such as parental expectations, rather than personal inclination (5). Therefore, extensive research is necessary to address this issue, enabling students to prepare effectively and thrive in these critical exams. Easily accessible counselling services should also be provided to pre-medical students to help manage stress and prevent burnout.